Cost-Effective Treatment of Hemihydrate Phosphogypsum and Phosphorous Slag as Cemented Paste Backfill Material for Underground Mine - Xilong Xue; Yuxian Ke; Qian Kang; Qinli Zhang; Chongchun Xiao; Fengjian He; Qing Yu (Advances in Materials Science and Engineering)
The environmental pollution caused by the discharge of phosphogypsum (PG) and phosphorous slag (PS) is a common issue for all countries. In order to fully utilize hemihydrate PG (HPG) and PS and treat goafs in mines, the HPG and PS were used as cementitious materials for cemented paste backfill (CPB). The physical and chemical properties of HPG and PS were first analyzed, and then, the characteristics of CPB were evaluated through fluidity tests, gas detection, uniaxial compressive strength (UCS) tests, bleeding tests, and scanning electron microscopy (SEM). After this, the underground environmental impact of CPB-based HPG and PS was investigated through a dynamic leachability experiment. The results show that (1) the UCS of CPB increases with the increase of the HPG content and mass fraction, and the addition of 3% quicklime can eliminate CO2, H2S, and SO2 generated from the slurry of CPB-based HPG-PS; (2) the addition of 3% quicklime and 5% cement to the HPG-PS mixtures can offset the strength loss of CPB in the late curing stage; (3) the UCS of the recommended specimen reaches 1.15–3.32 MPa after curing from 7 to 28 days, with their slump values varying from 15 mm to 26 mm, and the bleeding rates between 0.87% and 1.15%, which can meet the technical requirements of mining methods; (4) the UCS of CPB is the result of the cohydration reaction of hemihydrate gypsum (HG) in HPG and active Al2O3 and SiO2 in PS; and (5) the leaching indexes meet Category IV of the Chinese Groundwater Quality Standard (DZ/T 0290-2015). The results of this investigation provide a cost-efficient way for the efficient mining of phosphate resources and the comprehensive utilization of HPG and PS.